Tingkat Kemampuan Membaca Cepat Dengan Menggunakan Teknik Skimming Pada Mata Pelajaran Bahasa Indonesia Siswa Kelas V Di SDN Bonto Baddo Tolo Kabupaten Jeneponto - Syukriady, Dwi; Tumpu, Abu Bakar (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2024)
This study aims to determine the level of speed reading ability using skimming technique in Indonesian Language Subject of Fifth Grade Students at Bonto Baddo Tolo Kelara Elementary School, Jeneponto Regency. The type of research used is descriptive qualitative type. The subjects to be studied in this study were fifth grade students at Bonto Baddo Tolo Elementary School, Kelara District, Jeneponto Regency. The sample was 16 students. The data collection technique in the study was the test technique and observation sheet. The research instrument was the test material and test tools, while the data analysis technique in this study was the results of reading speed, reading comprehension, and calculating the overall average. Based on the results of the study, it can be concluded that overall the reading speed was 211 wpm, which is included in the good category. So the percentage of overall student understanding is 85%. So, the average ability to speed read using skimming technique of fifth grade students at Bonto Baddo Tolo Elementary School, Kelara District. Kelara, Jeneponto Regency is categorized as very good.